Different SPECT findings before and after Capgras’ syndrome in interictal psychosis - Horikawa, Hideki; Monji, Akira; Sasaki, Masayuki; Maekawa, Toshihiko; Onitsuka, Toshiaki; Nitazaka, Yoko; Hirano, Yoji; Hirano, Shougo; Hashioka, Sadayuki; Kato, Takahiro; Yoshida, Ichiro; Kanba, Shigenobu (Epilepsy & behavior, 2006)
We herein report a case of Capgras’ syndrome observed in interictal psychosis in which the single-photon emission computed tomography (SPECT) findings before and after the appearance of the psychotic symptoms differed. SPECT with 99mTc-hexamethyl propyleneamine oxine (HMPAO) revealed worsening of hypoperfusion in the entire right hemisphere after onset of the psychotic symptoms. The enhanced hypoperfusion demonstrated by SPECT in the present case seems to indicate a right interhemispheric disconnection resulting in the occurrence of Capgras’ syndrome.